Pentecostalism, Politics, and Prosperity in South Africa - Frahm-Arp, Maria (Religions, 2018)
One of the fastest growing religious movements in South Africa is a form of Pentecostal Charismatic Evangelic (PCE) Christianity that has some version of prosperity theology as a central pillar. This paper, based on sermons and interviews with 97 PCE pastors in the area of Johannesburg, South Africa, argues that these churches form loose clusters defined by similar emphases along a continuum of prosperity theology. These clusters are “abilities prosperity,” “progress prosperity,” and “miracle prosperity.” Some churches fall neatly into one of the clusters, while others appear as more of a hybrid between two of these types. The paper shows that a relationship exists between the type of theology preached by PCE churches and the nature and extent of the political engagement that the pastors suggested that members in these churches should have.
free